Allergic rhinitis, atopic dermatitis, and asthma are associated with differences in school performance among Korean adolescents - Kim, So Young (PLoS One, 2017)
Several studies have reported negative relations between allergic diseases and school performance but have not simultaneously considered various allergic diseases, including allergic rhinitis, asthma, and atopic dermatitis, and only examined a limited number of participants. The present study investigated the associations of allergic rhinitis, asthma, and atopic dermatitis with school performance in a large, representative Korean adolescent population. A total of 299,695 7th through 12th grade students participated in the Korea Youth Risk Behaviour Web-based Survey (KYRBWS) from 2009 to 2013. The subjects’ history of allergic rhinitis, asthma, and atopic dermatitis and number of school absences due to these diseases in the previous 12 months were examined and compared. School performance was classified into 5 levels. The relations between allergic disorders and school performance were analyzed using multiple logistic regressions with complex sampling and adjusted for the subjects’ durations of sleep, days of physical activity, body mass indexes (BMIs), regions of residence, economic levels, parents’ education levels, stress levels, smoking status, and alcohol use. A subgroup analysis of the economic groups was performed. Allergic rhinitis was positively correlated with better school performance in a dose-dependent manner (adjusted odds ratios, AOR, [95% confidence interval, CI] = 1.50 [1.43–1.56 > 1.33 [1.28–1.38] > 1.17 [1.13–1.22] > 1.09 [1.05–1.14] for grades A > B > C > D; P < 0.001). Asthma was negatively correlated with better school performance (AOR [95% CI] = 0.74 [0.66–0.83], 0.87 [0.79–0.96], 0.83 [0.75–0.91], 0.93 [0.85–1.02] for performance A, B, C, and D, respectively; P < 0.001). Atopic dermatitis was not significantly correlated with school performance. The subgroup analysis of the students’ economic levels revealed associations between allergic diseases and school performance. Compared to other allergic disorders, the asthma group had more school absences due to their symptoms (P < 0.001). School performance was positively correlated with allergic rhinitis and negatively correlated with asthma in Korean adolescents, even after adjusting for other variables. The asthma group had an increased number of school absence days, which presumably contributes to these students’ poor school performance.